2003
DOI: 10.1128/aem.69.5.2831-2841.2003
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Cloned Cyclopropane Fatty Acid Synthase Gene Reduces Solvent Formation in Clostridium acetobutylicum ATCC 824

Abstract: The cyclopropane fatty acid synthase gene (cfa) of Clostridium acetobutylicum ATCC 824 was cloned and overexpressed under the control of the clostridial ptb promoter. The function of the cfa gene was confirmed by complementation of an Escherichia coli cfa-deficient strain in terms of fatty acid composition and growth rate under solvent stress. Constructs expressing cfa were introduced into C. acetobutylicum hosts and cultured in rich glucose broth in static flasks without pH control. Overexpression of the cfa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 55 publications
4
78
0
Order By: Relevance
“…However, the increase in cyclopropane fatty acid production during [C 2 mim]Cl exposure demonstrates the distinct effect of ionic liquid on the bacterium. A number of studies using E. coli and lactobacilli have demonstrated that methylation of the cis-acyl chain double bond to form a cyclopropane ring plays a significant role in tolerance to acid, salt, butanol, and other stressors by reducing membrane fluidity and decreasing permeability (50)(51)(52)(53)(54). It is probable that cyclopropane fatty acid production plays a similar role in [C 2 mim]Cl tolerance by stabilizing the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…However, the increase in cyclopropane fatty acid production during [C 2 mim]Cl exposure demonstrates the distinct effect of ionic liquid on the bacterium. A number of studies using E. coli and lactobacilli have demonstrated that methylation of the cis-acyl chain double bond to form a cyclopropane ring plays a significant role in tolerance to acid, salt, butanol, and other stressors by reducing membrane fluidity and decreasing permeability (50)(51)(52)(53)(54). It is probable that cyclopropane fatty acid production plays a similar role in [C 2 mim]Cl tolerance by stabilizing the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…However, expression of the putative kinA is higher in the butanolstressed 824(pSOS95del) culture. Alterations in cell membrane composition are the most established mechanism which cells utilize to adapt to high levels of solvents (58). The ability of cells to incorporate a higher percentage of transmembrane fatty acids (long-chain C 30 fatty acids) in the cell membrane has been shown to increase alcohol tolerance in Thermoanaerobacter ethanolicus (7) from 1.5 to 8% (vol/vol) ethanol.…”
Section: Discussionmentioning
confidence: 99%
“…The highly differentially regulated gene expression patterns for the entire fatty acid biosynthesis operon and several related genes provide clear evidence that butanol stress alters the regulation of the fatty acid biosynthesis machinery. Increased expression of the cyclopropane fatty acid synthase gene (cfa [CAC0877]) in C. acetobutylicum has been shown to result in butanol resistance (58). Elevated expression of cfa was observed early in the high-dose 824(pSOS95del) culture, while cfa was Ͻ1.7 times higher in the high-dose 824 (pGROE1) culture (Fig.…”
mentioning
confidence: 99%
“…Prior to transformation into C. acetobutylicum, plasmid DNA must be methylated by the ⌽3TI methyltransferase to prevent restriction by the clostridial endonuclease Cac824I (24). Methylation was achieved by transformation of the required plasmid into E. coli DH10␤ harboring vector pDHKM (43), which carries an active copy of the ⌽3TI methyltransferase gene. Electrotransformation of wild-type C. acetobutylicum or strain SKO1 was carried out according to the protocol developed by Mermelstein et al (23).…”
Section: Methodsmentioning
confidence: 99%